A difusão da orientação empreendedora como elemento integrante da cultura organizacional: um estudo na UFSM - Lopes, Dilvan Maurício (2023)
This study aimed to analyze the scope of Entrepreneurial Orientation (EO) dimensions in the satellite campuses of the Federal University of Santa Maria (UFSM) and, based on the results, propose actions to promote their interrelation with the organizational culture of the institution. The theoretical framework encompassed three main topics: entrepreneurship in the public sector, entrepreneurial orientation, and organizational culture. The data collection procedure took place in two distinct stages: in the first quantitative stage, a survey with 23 closed-ended questions was administered to the employees stationed at the satellite campuses of UFSM. In the second qualitative stage, semi-structured interviews were conducted with the campus managers of Cachoeira do Sul, Frederico Westphalen, Palmeira das Missões, as well as representatives from the Pro-Rectorates of Entrepreneurship and Innovation, and Personnel Management. The data analysis procedure consisted of two stages. In the first stage, the quantitative one, descriptive analysis techniques and tests of reliability and internal consistency of data from the dimensions of innovation, proactivity, risk-taking, autonomy and competitive aggressiveness. In the second stage, the qualitative analysis was performed using content analysis. The survey results revealed the presence of incipient entrepreneurial orientation traits in the investigated campuses. From the employees' perspective, among the five dimensions studied, "Proactivity" obtained the highest evaluation level. Additionally, the interviews provided insights into the barriers and strategies for disseminating entrepreneurial orientation, as perceived by the campus managers. Based on the analysis of the results, actions were proposed to enhance the interrelation between entrepreneurial orientation and the organizational culture of the institution.